PENGGUNAAN SISTEM INFORMASI GEOGRAFIS DALAM PENGELOLAAN DAERAH ALIRAN SUNGAI MENGGUNAKAN MODEL SOIL AND WATER ASSESMENT TOOL (SWAT) - Nurdin Nurdin; Muhammad Shalahuddin; Fakhri Fakhri; Ermiyati Ermiyati; Alfian Malik; Horas Saut MM (Program Pascasarjana Universitas Riau, 2022)
The Soil and Water Assessment Tool (SWAT) model which is integrated with the Geographic Information System (GIS) can provide an overview or prediction of the influence of land management on watershed hydrology in accordance with the interests of evaluating and monitoring watershed management activities. The purpose of this study was to analyze the management of the Bukit Suligi Micro sub-watershed based on land use patterns, as a basis for determining the best recommendations for Forest and Land Rehabilitation activities by planting forestry trees based on community participation in Sei Kuning Village, Tandun District, Rokan Hulu Regency. The research method is processing primary and secondary data using a SWAT model integrated with GIS in analyzing hydrological characteristics in land use scenarios in the management of the Bukit Suligi Micro Watershed, as a basis for determining the best recommendations in Forest and Land Rehabilitation (RHL). community participation-based forestry tree planting activities in the Village. The best option in the land use scenario is the second scenario, which in its implementation in the field is the application of agroforestry to the existing Protected Forest Rehabilitation, only needing to insert forest plants based on community participation in Sei Kuning Village, Tandun District, Rokan Hulu Regency.